At home in the world : reflections on belonging while wandering the globe : an adventure across 4 continents with 3 kids, 1 husband, and 5 backpacks - Oxenreider, Tsh, 1977- (Thomas Nelson, 2017)
"As Tsh Oxenreider, author of Notes From a Blue Bike, chronicles her family's adventure around the world--seeing, smelling, and tasting the widely varying cultures along the way--she discovers what it truly means to be at home. In her late thirties and asa mom to three kids under age ten, Tsh Oxenreider and her husband decided to spend a rather ordinary nine months in an extraordinary way: traveling the corners of the earth to see, together, the places they've always wanted to explore. This book chronicles their global journey from China to Thailand to Australia, Sri Lanka, Uganda, France, Croatia, and beyond, as they fill their days with train schedules, world-schooling the kids, and working from anywhere. Told with wit and candor, Oxenreider invites uson a worldwide adventure without the cost of a ticket; to discover people, places, and stories worth knowing about; to find peace in the places we call home; and to learn that, as the Thai say, in the end, we are all 'same same but different'"--